CT‐determined low skeletal muscle mass predicts worse overall survival of gastric cancer in patients with cachexia. (18th July 2022) - Wan, Qianyi; Wang, Zhetao; Zhao, Rui; Tu, Tingting; Shen, Xiaoding; Shen, Yuhou; Li, Tao; Chen, Yi; Song, Yinghan
Abstract: Background: There were controversies for the association between computed tomography (CT)‐determined low skeletal muscle mass (SMM) and overall survival (OS) in gastric cancer (GC). In this study, we investigated whether cachexia could be a potential confounding variable for this issue. Methods: We retrospectively collected the patients of GC in our institution between July 2016 and January 2021. Preoperative SMM was determined by analyzing the skeletal muscle index of L3 with abdominal CT, and the cut‐offs for low SMM were defined as <52.4 (men) and < 38.5 cm 2 /m 2 (women), respectively. Overall survival (OS) was the primary endpoint. Results: Of the 255 included GC patients, 117 (46%) were classified as having low SMM. Those with low SMM were associated with a higher level of circulating interleukin 6 and C reactive protein but a lower level of albumin than those of normal SMM. The univariate analysis showed that low SMM, tumor‐node‐metastasis (TNM) stage, body mass index (BMI), postoperative chemotherapy, and cachexia were significantly associated with OS, while in the multivariate analysis, only low SMM and TNM stage were significantly associated with OS. Kaplan–Meier survival curves with log‐rank tests indicated that low SMM significantly predicted worse OS of GC. After grouping by cachexia, the low SMM significantly predicted worse OS in patients with cachexia instead of those without cachexia. Conclusions: CT‐determined low SMM predicts worse OS of GC in patients with cachexia instead of those without cachexia, and greater attention should be paid to such patients with synchronous low SMM and cachexia. Abstract : CT‐determined low skeletal muscle mass predicts worse overall survival of gastric cancer in patients with cachexia instead of those without cachexia. Greater attention should be paid to such patients with synchronous low skeletal muscle mass and cachexia.